MOTIVATIONAL INTERVIEWING TO PROMOTE COMMUNICATION FOR ADVANCE CARE PLANNING AMONG LATINOS - Nedjat-Haiem, F (Innov Aging, 2018)
Advance care planning (ACP) does not readily occur in medical settings, particularly among older Latinos. This study explored satisfaction with counseling to encourage readiness to engage in ACP among older Latinos (>50years) with advanced chronic diseases. Qualitative interviews were conducted post-intervention with older Latinos (N=32) who received ACP education plus motivational interviewing (MI) counseling. The data were analyzed using Prochaska’s stages of change framework. The average age of the sample was 65; 74% were women; half were from the U.S. or Mexico. More than half had either < 6th grade or < than high school education. Thematic analysis found that participants were in varied stages of readiness to engage in ACP with family and health care providers, including precontemplation, contemplation, preparation, action and maintenance. We will discuss motivational interviewing as a technique with older Latinos to increase engagement in ACP.